Psychometric validation of the Persian version of the howRwe questionnaire: a cross-sectional study - Mohammad Gholamnezhad; Leila Ghamkhar; Nezam Armand; Mohammad Effatpanah; Tim Benson; Mojtaba Sedaghat; Samane Hajiabbasi; AmirAli Ghamkhar; Seyed Yasin Yazdi-Amirkhiz; Maryam Ghamkhar (Journal of Patient-Reported Outcomes, 2026)
Abstract Background The howRwe questionnaire is a brief measure of patient experience that has not been adapted for Persian-speaking populations. This study aimed to translate, culturally adapt, and psychometrically validate the Persian version of the howRwe questionnaire (P-howRwe). Methodology This single-center cross-sectional study was conducted in two phases: translation/cultural adaptation and psychometric validation. Following forward and backward translation, an expert committee reviewed the translated version and produced a pre-final Persian version, which was refined through pilot testing. Psychometric properties were evaluated in 200 inpatients in Tehran, Iran. Test-retest reliability was assessed in 50 patients over a 5- to 7-day interval. Internal consistency was assessed using Cronbach’s alpha, content validity using the content validity ratio (CVR) and content validity index (CVI), and concurrent validity using the Persian SERVQUAL questionnaire. Construct validity was assessed by exploratory factor analysis and mirror exploratory factor analysis in two random subsamples. Results The Persian version showed good acceptability, with no reported comprehension difficulties during pre-final testing. The mean total P-howRwe score was 10.62 ± 1.32 (range 1–12). It demonstrated satisfactory reliability (Cronbach’s α = 0.84; McDonald’s ω = 0.86; ICC = 0.80, 95% CI: 0.76–0.85) and strong content validity, as assessed by a panel of 10 experts (CVR = 0.93–1.00; S-CVI/Ave = 0.95). Concurrent validity was supported by a significant positive correlation with Persian SERVQUAL scores ( r = 0.75, p < 0.01). Exploratory factor analysis identified a single factor explaining 69.28% of the total variance, with CR = 0.86 and AVE = 0.63. Mirror exploratory factor analysis in two random subsamples yielded comparable one-factor solutions, supporting structural stability. Conclusions The P-howRwe is a brief, culturally appropriate, and psychometrically sound instrument for assessing patient experience in similar Persian-speaking tertiary inpatient settings. Further validation in other healthcare contexts is warranted.